Confederate Saboteurs : Building the Hunley and Other Secret Weapons of the Civil War - Ragan, Mark K. (Book collections on Project MUSE., 2015)
Facing an insurmountable deficit in resources compared to the Union navy, the Confederacy resorted to unorthodox forms of warfare to combat enemy forces. Perhaps the most energetic and effective torpedo corps and secret service company organized during the American Civil War, the Singer Secret Service Corps, led by Texan inventor and entrepreneur Edgar Collins Singer, developed and deployed submarines, underwater weaponry, and explosive devices. The group's main government-financed activity, which eventually led to other destructive inventions such as the Hunley submarine and behind-enemy-line.